Analysis of Students’ Critical Thinking Abilities Through the Numbered Heads Together (NHT) Cooperative Learning Model on the Topic of Buffer Solutions - Ghea Paki Agustin; Afrizal Afrizal; Irwanto Irwanto (Scientia Publica Media, 2024)
The purpose of this study was to analyze the indicators of students’ critical thinking skills through the NHT type cooperative learning model on the buffer solution material. The research subjects were 36 students of class XI MIA 2 academic year 2019/2020 at SMAN 45 Jakarta. The research was conducted using qualitative analysis methods by collecting data through observation, discussion sheets, critical thinking skills analysis tests, reflective journals, and student interviews. The research was carried out by applying the NHT cooperative learning model in four meetings through 5 stages of learning, namely conveying goals and motivating students, presenting information, organizing students into groups, guiding study groups, evaluating and giving awards. The results showed that the critical thinking skills of students mostly showed satisfactory criteria. This is evidenced by the achievement of satisfactory criteria on aspects of problem identification in questions, aspects of conceptual understanding, aspects of the ideas connection, aspects of assumptions and aspects of drawing conclusions. The application of the NHT type of cooperative learning model has a positive impact on the development of students’ critical thinking skills through group discussion activities. The conclusion of the study shows that the critical thinking skills of students who achieve satisfactory criteria include three aspects including identification of the problem in question, conceptual understanding and drawing conclusions. Meanwhile, indicators that reach very good criteria contain aspects of the ideas connection and indicators that achieve unsatisfactory criteria contain aspects of assumption.